2018
DOI: 10.1210/jc.2017-02153
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Diversity in Women With Polycystic Ovary Syndrome Correlates With Hyperandrogenism

Abstract: These results suggest that hyperandrogenism may play a critical role in altering the gut microbiome in women with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
228
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(270 citation statements)
references
References 40 publications
16
228
3
1
Order By: Relevance
“…With regards to PCOS, several recent studies reported that changes in the gut microbiome are associated with PCOS (2326). These studies detected lower alpha diversity and differences in the relative abundances of specific Bacteroidetes and Firmicutes in women with PCOS compared to control individuals (2325). In particular, decreases in the relative abundance of Bacteroides and genera from the Ruminococcaceae and S24-7 families were observed in several studies.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…With regards to PCOS, several recent studies reported that changes in the gut microbiome are associated with PCOS (2326). These studies detected lower alpha diversity and differences in the relative abundances of specific Bacteroidetes and Firmicutes in women with PCOS compared to control individuals (2325). In particular, decreases in the relative abundance of Bacteroides and genera from the Ruminococcaceae and S24-7 families were observed in several studies.…”
Section: Introductionmentioning
confidence: 83%
“…In particular, decreases in the relative abundance of Bacteroides and genera from the Ruminococcaceae and S24-7 families were observed in several studies. In addition, changes in the gut microbiome correlated with hyperandrogenism (25), suggesting that testosterone may influence the composition of the gut microbiome in females. In addition to studies in humans, several studies reported a significant association between the gut microbiome and PCOS in rodent models (27, 28).…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of glucose intolerance, type 2 diabetes, obesity, dyslipidemia and metabolic syndrome are increased in PCOS. [3][4][5][6][7] Alterations of gut microbiota or dysbiosis may affect various host metabolic pathways through microbiota-derived metabolites and can play a role in the development of diabetes, obesity and cardiovascular disease. However, whether this increased cardiovascular risk at young age translates into premature or higher morbidity or mortality later in life is yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…2 Recent animal and human data in PCOS showed alterations in composition of gut microbiota in PCOS, partly associated with androgen excess. [3][4][5][6][7] Alterations of gut microbiota or dysbiosis may affect various host metabolic pathways through microbiota-derived metabolites and can play a role in the development of diabetes, obesity and cardiovascular disease. 8,9 Trimethylamine N-oxide (TMAO)…”
Section: Introductionmentioning
confidence: 99%
“…To date, a few observational studies on the gut microbiome of individuals with PCOS exist [20,22,28,42,43]. Bifidobacterium intake resulted in lower insulin concentration, insulin resistance and higher insulin sensitivity in patients after a 12-week intervention [44].…”
Section: Discussionmentioning
confidence: 99%